EFEITO DO EXERCÍCIO FÍSICO NA EXPRESSÃO E ATIVIDADE DO GLP-1 E NA EXPRESSÃO DE ADIPOCINAS EM RATOS OBESOS - Svidnicki, Paulo Vinicius (2013)
Metabolic syndrome is characterized by the presence of some risk factors that occur simultaneously in obese subjects, such as Type 2 diabetes mellitus, dyslipidemia and hypertension. GLP-1 is an important incretin that stimulates insulin secretion. Adipose tissue is considered an active complex and endocrine tissue, which secretes factors, termed adipokines, which by means of a dynamic signaling pathways involved in important biological energy balance, nutrient metabolism and immune system. Studies indicate that regular physical activity is related to the prevention and treatment of obesity. This study evaluated the effects of exercise training on the expression of adipokines collected following visceral adipose tissue: adiponectin, TNF alpha, PPAR gamma and PPAR alpha. In addition, we evaluated the expression of GLP-1 in the distal ileum and the insulinotropic action of this incretin in the pancreatic islets. The animal model used in this study were obese mice treated with monosodium glutamate (MSG) during the neonatal period, causing the animals to develop obesity in adulthood. The animals were divided into four groups: sedentary MSG, MSG exercised, sedentary controls, and controls exercised. Animals of exercise groups were submitted to swimming. At 90 days, the animals were sacrificed, biometric and biochemical parameters were analyzed pancreatic islets were isolated and sections of mesenteric fat and distal ileum assays were stored for qRT-PCR (Quantitative Real-Time Polymerase Chain Reaction) and immunohistochemistry. Our data show that regular physical activity and early improves obesity-related pathologies presented by MSG-obese mice. Exercised animals showed a decrease in adipocyte hypertrophy, leading to a change in the expression of adiponectin and PPAR alpha, which may have contributed to an improvement in energy homeostasis in these animals, however it has been shown that exercise does not correct completely the inflammatory profile in this obesity model. For the first time, demonstrated that exercise showed no direct action on the potentiation of insulin by GLP-1 stimulated by pre-prandial glucose, and no increase in the expression of incretin in exercised animals. Physical training reduced these parameters in animals only in mice CON-EXE. Regardless of the condition (fasting or glucose) and activity (exercised or sedentary) MSG treatment had no effect on expression of GLP-1 in the ileum. The swimming induced a reduction in the accumulation of adipose tissue and preserved glucose homeostasis in obese MSG rats, most likely by directly modulating the insulinotropic action of GLP-1 or its response in the pancreatic islets. Physical training inhibited the action of GLP-1 in the presence of low concentrations of glucose. However, physical training was able to restore the insulinotropic action of GLP-1 in the presence of high glucose concentration in MSG obese mice.